2003
DOI: 10.1002/pse.143
|View full text |Cite
|
Sign up to set email alerts
|

Special metals for seismic retrofitting of steel buildings

Abstract: Novel metals such as aluminium alloys, stainless steels and shape memory alloys can be used for the retrofitting of steel buildings in seismic areas. Therefore, it is useful to investigate their mechanical and physical properties along with the key issues of the material modelling. The present paper focuses on the mechanical response of such metals which are inherent to the seismic design. Furthermore, it compares their mechanical characteristics in order to assess (i) the relative merits; and (ii) the cost‐ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 32 publications
(49 reference statements)
0
10
0
Order By: Relevance
“…The CR97.5 sample with the strongest recrystallization texture shows the largest superelastic strain of 0.025, which is similar to that of the Ti–Nb‐based superelastic alloys . The comparison of yield stress in different alloy systems is presented in Figure b . The current non‐equiatomic NCATB‐HEA exhibits the highest yield stress among all the superelastic alloys.…”
Section: Resultsmentioning
confidence: 69%
See 1 more Smart Citation
“…The CR97.5 sample with the strongest recrystallization texture shows the largest superelastic strain of 0.025, which is similar to that of the Ti–Nb‐based superelastic alloys . The comparison of yield stress in different alloy systems is presented in Figure b . The current non‐equiatomic NCATB‐HEA exhibits the highest yield stress among all the superelastic alloys.…”
Section: Resultsmentioning
confidence: 69%
“…The amount of energy can be calculated as the area enclosed by the hysteresis loop in the stress–strain curves. Figure shows the energy absorbed in a single superelastic “loading‐unloading” cycle for NCATB‐HEA, in comparison to polycrystalline NiTi, Cu–Al–Ni, and Fe–Mn–Al–Ni alloys . The largest energy absorbed by one superelastic cycle for NCATB‐HEA with tensile strain of 0.04 is over 15 MJ m −3 , which is as large as that in the NiTi alloy with applied strain of 0.06, nearly four times larger than that in the Fe–Mn–Al–Ni alloy, and nearly 10 times larger than the Cu–Al–Ni alloy.…”
Section: Resultsmentioning
confidence: 99%
“…Di Sarno et al [18] and Di Sarno and Elnashai [19] have also recently shown that the use of stainless steel can provide up to 3 times the ultimate strain than carbon steels and they can exhibit improved post-local buckling giving them excellent application in seismic regions both for new structures and as braces for rehabilitating structures.…”
Section: Stainless Steelmentioning
confidence: 96%
“…weak-beam, strong-column response for moment resisting frames, whereby the column is designed not for the applied action but for action consistent with the over-strength of the beam. (iv) SS generally exhibits rather greater increases in strengths at fast rates of loading [5,9]. The initial stress state of the material has an effect on the strain rate.…”
Section: Stainless Steel and Seismic Designmentioning
confidence: 99%
“…Innovative metal materials that can be used for retrofitting of steel structures are aluminium alloys, shape memory alloys, and stainless steels. These metals possess unusual characteristics that render them suitable in the field of seismic rehabilitation [5]. These characteristics include The present work analyses the feasibility of the application of SSs for seismic retrofitting of steel structural systems for multi-storey buildings.…”
Section: Introductionmentioning
confidence: 99%